2008
DOI: 10.1007/s11010-008-9705-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of short-term administration of dl-α-lipoic acid on oxidative vulnerability induced by Aβ amyloid fibrils (25–35) in mice

Abstract: Abeta amyloid peptide is believed to induce oxidative stress leading to inflammation, which is postulated to play a significant role in the toxicity of Alzheimer's disease (AD). This study was designed to investigate the inhibitory effects of DL-alpha lipoic acid (LA), a potential free radical scavenger, on oxidative vulnerability induced by intraperitoneal injection of Abeta25-35 amyloid fibrils in mice. Mice were divided into three groups: control, Abeta amyloid toxicity induced (AT), and LA treated (ATL). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…We found that T6FA (10–25 µM) remarkably inhibited the auto-aggregation of Aβ (Figure 3). Given the toxicity of Aβ is mainly mediated by the prefibrillar oligomers of Aβ and Aβ-induced ROS [5][8], we hypothesized that T6FA could block the Aβ-induced cell death through its anti-oxidant activity and anti-aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that T6FA (10–25 µM) remarkably inhibited the auto-aggregation of Aβ (Figure 3). Given the toxicity of Aβ is mainly mediated by the prefibrillar oligomers of Aβ and Aβ-induced ROS [5][8], we hypothesized that T6FA could block the Aβ-induced cell death through its anti-oxidant activity and anti-aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Free-radical oxidative stress, particularly of neuronal lipids, proteins and DNA, is extensive in those AD brain areas in which Aβ is abundant and even those mild cognitive impairment brains [5][8], [37]. Our previous research demonstrated that T6FA has antioxidant activity determined by scavenging stable DPPH radicals [17], [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following transfection for 24 hr, Ab 25-35 was added into the normal 1640 medium at 0.015 mM concentration to model pathology of AD; serum deprivation that serum-free 1640 substituted the normal 1640 produced energy starvation and apoptosis. Here we use Ab 25-35 , a toxic antigenic fragment which exhibits all the biological activity of the full length Ab and has been earlier used by other researchers to study the neuronal toxicity and oxidative vulnerability [Jesudason et al, 2008]. Ab 25-35 is a convenient tool for the investigation of neurotoxic mechanisms involved in AD [Frozza et al, 2009].…”
Section: Cell Culture Transient Transfection and Treatment Of Cellsmentioning
confidence: 99%